Silage preparation and sustainable livestock production of natural woody plant - Du, Zhumei; Yang, Fuyu; Fang, Jiachen; Yamasaki, Seishi; Oya, Tetsuji; Nguluve, Damiao; Kumagai, Hajime; Cai, Yimin (Frontiers in Plant Science, 2023)
As the global population increases and the economy grows rapidly, the demand for livestock products such as meat, egg and milk continue to increase. The shortage of feed in livestock production is a worldwide problem restricting the development of the animal industry. Natural woody plants are widely distributed and have a huge biomass yield. The fresh leaves and branches of some woody plants are rich in nutrients such as proteins, amino acids, vitamins and minerals and can be used to produce storage feed such as silage for livestock. Therefore, the development and utilization of natural woody plants for clean fermented feed is important for the sustainable production of livestock product. This paper presents a comprehensive review of the research progress, current status and development prospects of forageable natural woody plant feed resources. The nutritional composition and uses of natural woody plants, the main factors affecting the fermentation of woody plant silage and the interaction mechanism between microbial co-occurrence network and secondary metabolite are reviewed. Various preparation technologies for clean fermentation of woody plant silage were summarized comprehensively, which provided a sustainable production mode for improving the production efficiency of livestock and producing high-quality livestock product. Therefore, woody plants play an increasingly important role as a potential natural feed resource in alleviating feed shortage and promoting sustainable development of livestock product.